Penegakan Hukum Dalam Pemutusan Hubungan Kerja Ditingkat Tripartit - Pardjer, Yolanda; Pattipawae, Dezonda Rosiana; Soplantila, Ronny (Jurnal Saniri, 2024)
Termination of Work Relations at the Tripartite Level is not accompanied by collaboration between mediators and labor inspectors, the implementation of supervision, and the application of administrative sanctions which causes the absence of protection to the rights of workers/laborers.  The method used in analyzing and discussing the problem is normative. The problem studied in this research is about the form of collaboration between mediators and labor inspectors in fulfilling law enforcement in the process of resolving industrial relations disputes between workers/laborers and employers through the tripartite level. As well as supervision and imposition of administrative sanctions to minimize violations that occur in the company, especially for the problem of termination of employment.  The results show that the government through mediators and labor inspectors can collaborate with employers who terminate employment, as well as Law Enforcement through supervision and imposition of administrative sanctions on employers who terminate employment at the tripartite level.